2017
DOI: 10.1021/acsnano.7b06263
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Doped Laser-Induced Porous Graphene Derived from Polysulfone-Class Polymers and Membranes

Abstract: Graphene based materials have profoundly impacted research in nanotechnology, and this has significantly advanced biomedical, electronics, energy, and environmental applications. Laser-induced graphene (LIG) is made photothermally and has enabled a rapid route for graphene layers on polyimide surfaces. However, polysulfone (PSU), poly(ether sulfone) (PES), and polyphenylsulfone (PPSU) are highly used in numerous applications including medical, energy, and water treatment and they are critical components of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
290
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(317 citation statements)
references
References 48 publications
18
290
0
Order By: Relevance
“…Heteroatom‐doped graphene has a tailored bandgap, which is different from pristine graphene that does not have a bandgap. This structure changes its electric and electrochemical properties, providing electrochemically active sites and increasing applicability for graphene . Two reasons for the increase of charge carrier density are that the structure would free more electrons of the sulfur and nitrogen penetration and structural defects .…”
Section: Resultsmentioning
confidence: 99%
“…Heteroatom‐doped graphene has a tailored bandgap, which is different from pristine graphene that does not have a bandgap. This structure changes its electric and electrochemical properties, providing electrochemically active sites and increasing applicability for graphene . Two reasons for the increase of charge carrier density are that the structure would free more electrons of the sulfur and nitrogen penetration and structural defects .…”
Section: Resultsmentioning
confidence: 99%
“…[ 86–89 ] Except for the polyimide, the laser‐induced graphene can also be deposited onto the poly(ether sulfone), polysulfone, and polyphenylsulfone under ambient conditions. [ 90 ] Meanwhile, N‐ and/or S‐doping could be accomplished simultaneously into the laser‐induced graphene owing to the intrinsic N and/or S content in the utilized polymers. Because of the high thermal stability, excellent electrical conductivity, and versatility of polymer substrate, laser‐induced 3D graphene and its related composites have been regarded as promising candidates for various applications.…”
Section: Synthesis Methods Of 3d Graphenementioning
confidence: 99%
“…Laser manufacturing has become increasingly popular in material fabrication due to its high throughput and patterning capability. Recently, it was demonstrated that a commercial CO 2 infrared laser scriber can be used to in situ form and pattern 3D porous graphene on polyimide (PI), cloth, paper, and food under ambient conditions. In comparison to the laser‐reduced graphene method, which uses a laser to reduce graphene oxide (GO) films to graphene, the new laser‐induced graphene (LIG) method avoids the use of GO precursors and directly exploits the substrate materials as a carbon source, which greatly simplifies the fabrication process and reduces the cost .…”
Section: Introductionmentioning
confidence: 99%